The Effect of Nb Supplement on Material Characteristics of Iron with Lamellar Graphite - Ahmet Oktay Devecili; Rifat Yakut (Advances in Materials Science and Engineering)
In this experiment a cast iron alloy consisting of 0.019, 0.151, 0.431, and 0.646% niobium by weight was set and the microstructure solidification of iron with lamellar graphite was provided. These alloys were subjected to an abrasion test and chemical analyses of the microstructure were done by using scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (EDS). In addition to this, phase compositions were characterised by X-ray diffraction (XRD). Tests of mechanical strength, hardness, and tension were also applied to the alloys. The results of this experiment demonstrated that the addition of niobium to iron with lamellar graphite caused an increase in the abrasion resistance by 15%. This experiment shows that adding niobium improves the mechanical properties of grey cast iron.